A novel quantitative morphometry approach to assess regeneration in dystrophic skeletal muscle - Buttgereit, Andreas; Weber, Cornelia; Friedrich, Oliver (Neuromuscular disorders, 2014)
Duchenne muscular dystrophy is an inherited degenerative muscle disease with progressive weakness of skeletal and cardiac muscle. Disturbed calcium homeostasis and signalling pathways result in degeneration/regeneration cycles with fibrotic remodelling of muscle tissue, sustained by chronic inflammation. In addition to altered microarchitecture, regeneration in dystrophic muscle fibres is often only classified by centrally located nuclei but correlation of the regeneration process to nuclear volumes, myosin amounts, architecture and functional quality are missing, in particular in old muscles where the regenerative capacity is exhausted. Such information could yield novel regeneration-to-function biomarkers. Here we used second harmonic generation and multi photon fluorescence microscopy in intact single muscle fibres from wild-type, dystrophic mdx and transgenic mdx mice expressing an Δex 17-48 mini-dystrophin to determine the percentage of centronucleated fibres and nucleus-to-myosin volume ratio as a function of age. Based on this ratio we define a ‘biomotoric efficiency’ as an optical measure for fibre maturation, which is close to unity in adult wild-type and mini-dystrophin fibres, but smaller in very young and old mdx mice as a result of ongoing cell maturation (young) and regeneration (aged). With these parameters it is possible to provide a quantitative measure about muscle fibre regeneration.